Current Musculoskeletal Pain and Injury History in Former NCAA Division I Female Athletes - Irene Kalbian; Miguel Escalon; Katharine Holmes; Rebecca Maitin (American Journal of Physical Medicine & Rehabilitation, 2026)
Objective: To determine the prevalence of current musculoskeletal pain among former NCAA Division I female athletes and examine associations with prior injury history, anatomical distribution of symptoms, and functional outcomes. Design: Cross-sectional web-based survey of former NCAA Division I female athletes. Participants completed questionnaires regarding athletic history, prior injuries, current pain, osteoarthritis diagnosis, physical activity, and PROMIS Pain Interference outcomes. Results: A total of 428 former NCAA Division I female athletes were included, of whom 305 (71.3%) reported current musculoskeletal pain. Athletes with pain were more likely to report injuries before college (71% vs. 46%), injuries during college (80% vs. 62%), continued training despite injury (73% vs. 55%), career-ending injuries (8.5% vs. 1.6%), and prior NSAID use (72% vs. 54%) (all P ≤0.008). Pre-collegiate injury (adjusted OR 2.84, 95% CI 1.72-4.68) and career-ending injury (adjusted OR 4.85, 95% CI 1.10-21.45) independently predicted current pain. Current pain was concentrated primarily in the knee, spine, and hip/pelvis. Despite frequent symptoms, 94% of participants remained physically active. Conclusion: Persistent musculoskeletal pain is common among former NCAA Division I female athletes and is associated with cumulative injury burden. Longitudinal studies are needed to better understand musculoskeletal health across the female athletic lifespan.